Indian dance (Bharatanatyam) to ease social loneliness and isolation in older adults - Sloka Iyengar (Critical Public Health)
Older adults worldwide are facing disproportionate levels of isolation and loneliness. The current frameworks for understanding social isolation and loneliness include factors such as the physical and mental health of the individuals, loss of friends and family, level of education, relationships, and the built environment. While these models are useful, they fail to consider the individual experiences of older adults holistically; as an example, they do not include older adults’ relationship with themselves as they navigate the many challenges of life. In this article, I propose a novel framework for describing social isolation and loneliness in older adults that includes relationships to their changing bodies and experiences, to history and literature, and to nature and current events. Considering this revised framework, I summarize my observations as a teaching artist using Bharatanatyam, a 2,000-year-old Indian traditional dance form, in alleviating loneliness and isolation. Outcomes are in the form of qualitative narratives that are thematically united and presented. Given the highly communicative and relational nature of Bharatanatyam, I hypothesize that immersion in Bharatanatyam will enable connections of various kinds. This article describes three ways in which Bharatanatyam is particularly well-suited to build connections; these are 1. Connection with oneself in body, mind, and psyche; 2. Connection to tradition and history and 3. A systematic structure of relating to others, to the nature and environment, and current events.